Serum Betaine and Dimethylglycine Are Higher in South Asian Compared with European Pregnant Women in Canada, with Betaine and Total Homocysteine Inversely Associated in Early and Midpregnancy, Independent of Ethnicity. Issue 12 (30th August 2019) - Mujica-Coopman, Maria F; Tan, Amy; Schroder, Theresa H; Sinclair, Graham; Vallance, Hilary D; Lamers, Yvonne
ABSTRACT: Background: As a methyl donor required in the folate–vitamin B-12 independent remethylation of total homocysteine (tHcy) to methionine, betaine is critical for fetal development. Pregnant South Asian women living in Canada had a higher reported prevalence of low vitamin B-12 status compared with Europeans; betaine concentrations in this population are unknown. Objectives: We aimed to compare serum betaine concentrations between South Asian and European pregnant women, and to determine the relation between betaine and tHcy concentrations in early pregnancy. Methods: A retrospective cohort study was conducted using biobanked serum samples of 723 apparently healthy pregnant women of South Asian (50%) and European ethnicity residing in British Columbia, Canada. Betaine, dimethylglycine (DMG), tHcy, and related metabolites were quantified in samples collected in the first (8–13 weeks of gestation) and second (14–20 weeks of gestation) trimesters. The relation between betaine and tHcy concentrations was assessed using a generalized regression model adjusted for weeks of gestation, ethnicity, prepregnancy BMI, maternal age, neonatal sex, parity, total vitamin B-12, folate, pyridoxal 5′-phosphate, and methionine concentrations. Results: Median serum concentrations of betaine and its metabolite DMG were higher in South Asian women in the first (19.8 [IQR: 16.3–25.0] and 1.55 [IQR: 1.30–1.96] μ mol/L , respectively) and second trimesters (16.1 [IQR: 12.9–19.8] and 1.42 [IQR: 1.14–1.81] μ mol/L , respectively) compared with European women (17.6 [IQR: 13.7–22.6] and 1.38 [IQR: 1.12–1.77] μ mol/L , respectively) and (12.9 [IQR: 10.6–16.7] and 1.19 [IQR: 0.97–1.52] μ mol/L , respectively; all P values < 0.0001). Betaine was inversely associated with tHcy concentration (β = −0.0208; 95% CI: −0.0341, −0.00742; P = 0.002). Additionally, total vitamin B-12 was associated with tHcy concentration (β = −0.0312; 95% CI: −0.0401, −0.0224), after adjusting for confounding factors. Conclusions: Pregnant South Asian women residing in Canada had higher betaine and DMG concentrations, compared with women of European ethnicity, while betaine and total vitamin B-12 predicted tHcy independent of ethnicity. Our results emphasize the role of betaine, as methyl donor, in the remethylation of tHcy in a folate-replete population.